2018
DOI: 10.3389/fvets.2018.00245
|View full text |Cite
|
Sign up to set email alerts
|

Review: Roles of Prebiotics in Intestinal Ecosystem of Broilers

Abstract: In recent years, prebiotics have been considered as potential alternatives to antibiotics. Mechanisms by which prebiotics modulate the ecosystem of the gut include alternation of the intestinal microbiota, improvement of the epithelium, and stimulation of the immune system. It is suggested that the administration of prebiotics not only influences these aspects but also regulates the interaction between the host and the intestinal microbiota comprehensively. In this review, we will discuss how each prebiotic am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 117 publications
4
133
0
9
Order By: Relevance
“…To date, only few in ovo studies reported the application of prebiotics in ovo [6,7]. Regarding the performance objectives (body weight, feed intake and feed conversion ratio, FCR), the results for different prebiotics or synbiotics are found to be inconsistent, but consequently supporting the stimulating effect on gut development [8], immune gene expression [9], and improved resistance [10].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only few in ovo studies reported the application of prebiotics in ovo [6,7]. Regarding the performance objectives (body weight, feed intake and feed conversion ratio, FCR), the results for different prebiotics or synbiotics are found to be inconsistent, but consequently supporting the stimulating effect on gut development [8], immune gene expression [9], and improved resistance [10].…”
Section: Introductionmentioning
confidence: 99%
“…The quality and composition of the meat are also affected by the treatment of birds during rearing and by supplementation with bioactive substances. It has already been proved that the administration of bioactive substances such as synbiotics [3], probiotics [4], and prebiotics [5] affects the rearing parameters and intestinal microbiota, which may indirectly affect meat quality. The gastrointestinal microbiota affects the host organism by regulating immune response, metabolism, digestion, and nutrient absorption [6].…”
Section: Introductionmentioning
confidence: 99%
“…The heightened potential of symbiotic formulations is accredited to mechanisms shared by both probiotics and prebiotics. Teng and Kim [33] have reported that prebiotics from inulin group might stimulate the growth and activity of beneficial bacteria by increasing the concentration of short-chain fatty acids and lactic acid in the ceca of broilers. It is worth highlighting that the intestinal colonization of LAB in poultry has been associated with reduction of pathogens, higher performance, and development of the immune system [8,14,34,35].…”
Section: Discussionmentioning
confidence: 99%